Implementation of RevoU Tech Academy's Independent Campus Program to Increase Digital Talent Capacity - Astriyani, Erna; Cholisoh, Novi; Amalia, Andiena; Syaputra, Harian (Journal Sensi: Strategic of Education in Information System, 2025)
The Merdeka Belajar Kampus Merdeka (MBKM) program aims to enrich students' hard and soft skills, preparing them better for the ever-changing challenges of the times. One of the independent study programs is RevoU Tech Academy "Learn Data Analytics & Software Development With AI" which focuses on developing skills in the fields of Data Analytics and Software Engineering. This journal describes the implementation of the RevoU Tech Academy program and its effects on participants using a qualitative descriptive approach. The program is conducted for 5 months, with a 17-week curriculum that covers Data Processing in Data Analytics, Data Visualization & Communication in Data Analytics with AI Tools, Introduction to Web Development, Front-End Development with AI Tools, and Career Development program. Participants are not only given lectures but also practice their knowledge through various assignments and a capstone project. The results of the study showed that the program was successful in developing participants' skills in Data Analytics and Software Engineering. They were able to clean data, analyze data, build visualizations, develop web applications.